Executive function and brain development in adolescents with severe congenital heart disease (Teen Heart Study): protocol of a prospective cohort study - Beatrice Latal; Melanie Ehrler; Nadja Naef; Ruth O'Gorman Tuura (BMJ Open)
Introduction Congenital heart disease (CHD) is the most frequent congenital malformation. With recent advances in medical care, the majority of patients with CHD survive into adulthood. As a result, interest has shifted towards the neurodevelopmental outcome of these patients, and particularly towards the early detection and treatment of developmental problems. A variety of mild to moderate cognitive impairments as well as emotional and behavioural problems has been observed in this population. However, a more detailed assessment of the various domains of executive function and their association with structural and functional brain development is lacking. Therefore, the current study will examine all domains of executive function and brain development in detail in a large sample of children and adolescents with CHD and healthy control children.Methods and analysis A total of 192 children and adolescents with CHD aged 10–15 years, who participated in prospective cohort studies at the University Children’s Hospital Zurich, will be eligible for this study. As a control group, approximately 100 healthy children will be enrolled. Primary outcome measures will include executive function abilities, while secondary outcomes will consist of other neurodevelopmental measures, including intelligence, processing speed, attention, fine motor abilities and brain development. An MRI will be performed to assess structural and functional brain development. Linear regression analyses will be applied to investigate group differences and associations between executive function performance and neurodevelopmental measures.Ethics and dissemination This study is supported by the Swiss National Science Foundation (SNF 32003B_172914) and approved by the ethical committee of the Canton Zurich (KEK 2019–00035). Written informed consent will be obtained from all the parents and from children aged 14 years or older. Findings from this study will be published in peer-reviewed journals and presented at national and international conferences for widespread dissemination of the results.